2022
DOI: 10.1371/journal.pone.0275775
|View full text |Cite
|
Sign up to set email alerts
|

Urinary pyrethroid metabolite and hearing threshold shifts of adults in the United States: A cross-sectional study

Abstract: Hearing loss (HL) is a global health problem with a high prevalence and profound socioeconomic impact. Pyrethroids are one of the most commonly used insecticides. Although previous studies have reported the relationship between pyrethroids and neurotoxicity, little is known about the effect of pyrethroid exposure on the auditory system among the general population. This study is aimed to investigate the association of pyrethroid exposure with hearing threshold shifts of adults in the United States. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The main characteristics of the studies carried out in humans are summarized in Table 1. Of the 13 studies included, 8 were performed on urine samples [30][31][32][33][34][35][36][37]; 1 on perilymph [38], 2 on plasma [39,40] and 2 on serum [41,42]. The most commonly used technique for metabolomic profiling was liquid chromatography coupled with mass spectrometry (LC-MS); while only one study was performed by Nuclear Magnetic Resonance (NMR) and two by Gas Chromatography-Mass Spectrometry (GC-MS).…”
Section: Metabolomic Profiling In Humans With Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the studies carried out in humans are summarized in Table 1. Of the 13 studies included, 8 were performed on urine samples [30][31][32][33][34][35][36][37]; 1 on perilymph [38], 2 on plasma [39,40] and 2 on serum [41,42]. The most commonly used technique for metabolomic profiling was liquid chromatography coupled with mass spectrometry (LC-MS); while only one study was performed by Nuclear Magnetic Resonance (NMR) and two by Gas Chromatography-Mass Spectrometry (GC-MS).…”
Section: Metabolomic Profiling In Humans With Hearing Lossmentioning
confidence: 99%
“…The study revealed a strong association between the exposure to these compounds and an increase in hearing thresholds. Similarly, Long & Tang [37] further investigated the ototoxicity induced by pyrethroid exposure in a large cohort of adults. In this case, an association between 3-PBA levels and both low and high frequencies hearing thresholds was described in subjects aged 20-39 years.…”
Section: Metabolomic Analysis On Urine Samplesmentioning
confidence: 99%